Archipelago Traditional House Application Based on Articulate Storyline 3 in Grade Five Elementary School - Dinis Puspita Dewi; Kurniana Bektiningsih (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
Traditional House learning material in content There are many Pancasila education lessons, causing results For students in low V classes. Study This aims to develop learning media from the Archipelago Traditional House Application based on Articulate Storyline 3 in class V elementary school. This research uses research and development (R&D) as a research method and ADDIE development model. Subject from study This is students, class teachers, and team experts. Data collection techniques used are test and non-test. The data analysis techniques used are descriptive qualitative and descriptive quantitative. Research data This was obtained through interviews, observations, and a questionnaire. Validation results in media experts of 92% and experts material of 91% show that The Archipelago Traditional House Application is very feasible to use. Learning outcomes pre-test and post-test show the average difference is 30, which means there are enhanced results for Study students. The average value obtained based on calculating the N-Gain score is 72%, which means the media is effective. For increased results, Study students. Response results show that media use by students is 92% and that of teachers is 90%, meaning the media is effective for application in learning. Therefore, the Archipelago Traditional House Application based on Articulate Storyline 3 is feasible for application in learning and can increase results For students in Class V Elementary School.